2017
DOI: 10.1055/s-0036-1589049
|View full text |Cite
|
Sign up to set email alerts
|

A Photochemical Two-Step Formal [5+2] Cycloaddition: A Condensation–Ring-Expansion Approach to Substituted Azepanes

Abstract: Seven-membered nitrogen-containing heterocycles are considerably underrepresented in the literature compared to their five- and six-membered analogues. Herein, we report a relatively understudied photochemical rearrangement of N-vinylpyrrolidinones to azepin-4-ones in good yields. This transformation allows for the conversion of readily available pyrrolidinones and aldehydes to densely functionalized azepane derivatives in a facile two step procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…We hypothesized that, among several possible pathways, nucleophilic attack by water on the γ-carbon of 3 would eventually release a “traceless” polypeptide product, together with an unsaturated aldehyde or decomposition product thereof. To explore this proposed pathway, a model vinylogous 2-nitrobenzyl amide ( 2 ) was prepared by analogy to a reported condensation . Upon treatment with 365-nm light in water in the presence of triethylamine as a scavenger, the conversion of caged amide 2 to N- methylacetamide ( 4 ) was monitored by 1 H NMR, based on the N- methyl resonance shift from 3.14 to 2.72 ppm upon photocleaveage .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that, among several possible pathways, nucleophilic attack by water on the γ-carbon of 3 would eventually release a “traceless” polypeptide product, together with an unsaturated aldehyde or decomposition product thereof. To explore this proposed pathway, a model vinylogous 2-nitrobenzyl amide ( 2 ) was prepared by analogy to a reported condensation . Upon treatment with 365-nm light in water in the presence of triethylamine as a scavenger, the conversion of caged amide 2 to N- methylacetamide ( 4 ) was monitored by 1 H NMR, based on the N- methyl resonance shift from 3.14 to 2.72 ppm upon photocleaveage .…”
mentioning
confidence: 99%
“…To explore this proposed pathway, a model vinylogous 2-nitrobenzyl amide (2) was prepared by analogy to a reported condensation. 30 Upon treatment with 365-nm light in water in the presence of triethylamine as a scavenger, the conversion of caged amide 2 to N-methylacetamide (4) was monitored by 1 H NMR, based on the N-methyl resonance shift from 3.14 to 2.72 ppm upon photocleaveage. 31 The clean and efficient photocleavage observed provides a sufficient foundation for a vinylogous approach to sp 2 C−N bond cleavage in complex polypeptides.…”
mentioning
confidence: 99%
“…Among these fluorous motifs, the 3,3,3‐trifluoropropen‐1‐yl group is relatively rare and methods which enable its incorporation into heterocycles through the formation of new C−N bond are hardly available and mostly limited to some specific substrates, such as cyclic amides [11] . The N ‐trifluoropropenylation of enamides such as pyrrolidin‐2‐one can be achieved through the palladium‐ [11a] or copper‐catalyzed [11b] trifluoromethylation of N ‐vinylpyrrolidin‐2‐one with CF 3 I or under photocatalytic conditions (Figure 1a), [11c–e] while the same product can be obtained with trifluoropropionaldehyde (Figure 1b) [11f] . The use of 3,3,3‐trifluoropropyne gas as a C 2 ‐CF 3 surrogate requires the handling of gaseous reagent, but it was successfully applied as Michael acceptor in its reaction with 2’‐deoxyiodouridine used for iodinated DNA bases (Figure 1c) [11g] .…”
Section: Figurementioning
confidence: 99%
“…An interesting follow up to the studies of the photochemical Fries rearrangement was presented by Rovis and coworkers in 2017. 10 The authors found that N -vinylpyrrolidinones undergo a [1,3] acyl shift after irradiation with UV-C light ( λ max 254 nm), to form azepin-4-ones (Scheme 1b).…”
mentioning
confidence: 99%
“…A plausible mechanism proposed for this reactivity involves the Norrish type I (α) homolytic cleavage of an amide bond by irradiation with 254 nm light (Scheme 3). 10,30 The resultant biradical II can then either recombine to reform the starting material I or combine with the carbon β to the nitrogen to generate imine IV . Tautomerization of IV gives the observed product V .…”
mentioning
confidence: 99%